Tingkat Pengetahuan Nelayan Pesisir Wendu Tentang Ikan Pari Gergaji (Pristis spp.) - Amir, Astaman; Makhfudin, Wisnu I.; Sianturi, Reny; Kaya, Ivonne R. G. (AGRICOLA, 2022)
This study aims to determine the level of knowledge of Wendu coastal fishermen’s about sawfish. This research was conducted in June 2021-March 2022. The sample in this study was 92 people, using the non-probability sampling method. The type of non-probability sampling used in this research is purposive sampling. Data analysis technique is done by combining quantitative and qualitative data analysis. The average knowledge of the habitat reaches 68%, food reaches 75%, uniqueness reaches 97%, the use of rostrum reaches 70%, handling if accidentally caught reaches 73%, utilization status reaches 62%, reasons for protection reach 75%, protection regulations reach 94%, overall the average level of knowledge of respondents reached 77%.